Extra-oral Halitosis - Neto, Carlos Firmino de Oliveira (2017)
Halitosis affects around 25% of the whole population and has a large social and economic impact. For the majority of patients suffering from bad breath, it causes embarrassment and affects their social communication and life. Dentists and periodontologists are the first-line professionals to be challenged with this problem, so they should be aware of the origin, the detection and the treatment of this pathology. But halitosis can be indicative of underlying diseases, requiring a multidisciplinary team approach. Depending on the place where it is originated, halitosis can be divided into intra-oral and extra-oral, whose treatment is much more complicated than for intra-oral halitosis. In this work, the origins of extra-oral halitosis were addressed, as well as the responsible sulfur compounds. Distinctive methods of detection of halitosis were focused and their advantages and disadvantages were highlighted. Gas differentiation methods as an auxiliary tool were emphasized in the diagnosis of halitosis type and, therefore, in its specific treatment. At last, different methods of treatment of extra-oral halitosis have been approached, from masking the bad breath to more invasive treatments.